Pharmacological Targeting of Vacuolar H+-ATPase via Subunit V1G Combats Multidrug-Resistant Cancer. Issue 11 (19th November 2020) - Wang, Yuezhou; Zhang, Lei; Wei, Yanling; Huang, Wei; Li, Li; Wu, An-an; Dastur, Anahita; Greninger, Patricia; Bray, Walter M.; Zhang, Chen-Song; Li, Mengqi; Lian, Wenhua; et al.
Summary: Multidrug resistance (MDR) in cancer remains a major challenge for the success of chemotherapy. Natural products have been a rich source for the discovery of drugs against MDR cancers. Here, we applied high-throughput cytotoxicity screening of an in-house natural product library against MDR SGC7901/VCR cells and identified that the cyclodepsipeptide verucopeptin demonstrated notable antitumor potency. Cytological profiling combined with click chemistry-based proteomics revealed that ATP6V1G directly interacted with verucopeptin. ATP6V1G, a subunit of the vacuolar H + -ATPase (v-ATPase) that has not been previously targeted, was essential for SGC7901/VCR cell growth. Verucopeptin exhibited strong inhibition of both v-ATPase activity and mTORC1 signaling, leading to substantial pharmacological efficacy against SGC7901/VCR cell proliferation and tumor growth in vivo . Our results demonstrate that targeting v-ATPase via its V1G subunit constitutes a unique approach for modulating v-ATPase and mTORC1 signaling with great potential for the development of therapeutics against MDR cancers. Graphical Abstract: Highlights: The natural product verucopeptin exhibits antitumor activity against MDR cancers Verucopeptin directly targets the v-ATPase ATP6V1G subunit Verucopeptin kills MDR cancer cells by inhibition of both v-ATPase and mTORC1 Verucopeptin suppresses MDR cancer progression in vivo Abstract : Alternative strategy for treating multidrug-resistant (MDR) cancer is needed. Wang et al. show that the natural product verucopeptin kills MDR cancer by targeting the ATP6V1G subunit of v-ATPase, which leads to strong inhibition of both v-ATPase activity and mTORC1 signaling.